An efficient calixarene-based functional material for the sorption and recovery of Cr(VI) from water. Issue 11 (2nd September 2019) - Khan, Shaheedullah; Qureshi, Imdadullah; Shifa, Muhammad Shahzad; Waziri, Arshad Hussain
ABSTRACT: The present study elaborates synthesis of calix[4]arene-functionalised resin (GX ) and its application in sorption of Cr(VI) from water. Effect of variation in pH was explored through batch study, which indicates that maximum sorption of 89% occurs at pH 4. Similarly, in dynamic mode, various parameters, i.e. change in concentration, flow rate and bed height, were optimised using Bed Depth Service Time (BDST) model. Based on the BDST model, maximum sorption capacity was found to be 85 mg g −1 at optimum conditions. The (GX ) is recoverable up to 97% and also has the potential to regenerate and reuse till six cycles.